An ethical assessment of computer ethics using scenario approach - Masrom, Maslin; Ismail, Zuraini; Hussein, Ramlah; Mohamed, Norshidah (Academy of Taiwan Information Systems Research, 2010)
Ethics refers to a set of rules that define right and wrong behavior, used for moral decision making. In this case, computer ethics is one of the major issues in information technology (IT) and information system (IS). The ethical behaviour of IT students and professionals need to be studied in an attempt to reduce many unethical practices such as software piracy, hacking, and software intellectual property violations. This paper attempts to address computer-related scenarios that can be used to examine the computer ethics. The computer-related scenario consists of a short description of an ethical situation whereby the subject of the study such as IT professionals or students, then rate the ethics of the scenario, namely attempt to identify the ethical issues involved. This paper also reviews several measures of computer ethics in different setting. The perceptions of various dimensions of ethical behaviour in IT that are related to the circumstances of the ethical scenario are also presented.